Oxidation Behavior of Multilayer Hard Coatings (TiCN/Al(2)O(3)/TiN) in Process of Recycling Coated Multicomponent Hardmetal Scrap - Kuang, Hai (Materials (Basel), 2018)
The coating is one of the biggest problems in the recycling of coated multicomponent hardmetal scraps. The isothermal oxidation behavior of WC-Co multicomponent cemented carbide inserts with a TiCN/Al(2)O(3)/TiN hard coating in the recycling process was investigated. The oxidation rate slowed down as the protective coating blocked element diffusion. A rapid oxidation rate was obtained when they were milled into powders and isothermally oxidized at 900 °C. A rapid path for element diffusion was provided by the defects, which were promoted by stress, expansion, and gas volatilization. Both the TiN and TiCN layers were oxidized to a porous TiO(2) scale, while the Al(2)O(3) phase remained and the dense Al(2)O(3) layer acted as a barrier for its good oxidation resistance. Pieces of the Al(2)O(3) layer were obviously seen in the final oxides. This provides critical information to reduce the negative effect of coatings and improve the performance of recycled WC powders and hard alloys.